Spasmolytic activity of essential oil from Lippia microphylla Cham. (Verbenaceae) is mediated by modulation of Ca2+ signaling on animal and cellular models (Research, Society and Development, 2021)
Lippia species (Verbenaceae) are widely used on folk medicine to treat respiratory and gastrointestinal disorders. In this work, we evaluated the relaxant effect of the essential oil from Lippia microphylla Cham. (LM‑EO) and its major components on guinea pig ileum as well as elucidate the involved mechanisms. LM-EO inhibited phasic contractions as well as relaxed tonic contractions induced by several contractile agents on guinea pig ileum. Similar results were observed in tests using thymol and carvacrol, the major constituents of LM-EO. Voltage-dependent calcium channel (CaV) blockade was suggested since LM-EO shifted to the right non parallelly CaCl2-induced cumulative contractions and confirmed when LM-EO relaxed the ileum pre contracted by S-(-)-Bay K8644, a selective CaV agonist. On circular layer, LM-EO inhibited phasic contractions, being equipotent to the effect observed in the intact ileum. In the myocytes from ileum longitudinal layer, LM-EO reduced fluorescence intensity induced by histamine, similarly to verapamil (CaV blocker), indicating a decrease in cytosolic concentration of Ca2+ ([Ca2+]c). In conclusion, LM-EO presents a spasmolytic activity on guinea pig ileum by CaV blockade and [Ca2+]c reduction. These results present a rationale for the use of L. microphylla as a potential product to intestinal disorders.